Begonia ludwigii and B. parcifolia (Begoniaceae) two new records to the Peruvian flora - Esquerre-Ibañez, Boris (2018)
Begonia ludwigii Irmscher and B. parcifolia C. DC. are newly recorded for the Peruvian flora, where they occur within the biodiverse Amotape-Huancabamba zone. Both species were originally considered to be endemic to Ecuador. Within Peru, B. ludwigii is reported from four populations in the Departments of Piura, Lambayeque and Cajamarca, while B. parcifolia is reported from three populations in the Departments of Tumbes, Piura and Cajamarca. Descriptions of B. ludwigii and B. parcifolia are provided and their distributions mapped and discussed. Information about their taxonomy and conservation status are also presented.